Feasibility of Creating a Continuous Greenway Network by Using the Capacity of Pedestrian Routes (Case Study: Shiraz) - Sara Pourkiani; Mojtaba Arasteh; Abdolhossein Zarifian Mehr (توسعه پایدار شهری, 2025)
Today, one of the basic issues of urban planners is the improvement of urban spaces, among which green use as a living and dynamic element plays an important role in this field. On the other hand, the correct identification of these spaces and their adaptation, considering the importance of gardens and green spaces in the city, leads to a distribution that is proportional to the size and power of the region. This action needs analysis and feasibility studies, which is a step in the direction of moving from the current situation to the desired situation. Gardens of Qasr al-Dasht, most of which are located within the six cities of Shiraz, are considered a valuable resource for improving the quality of the environment. The current research is an applied research and a combination of library and analytical methods, and its purpose is to provide a continuous network of greenways through the efficiency of pedestrian routes according to the current conditions of the six cities of Shiraz. The method used in this research is the multi-criteria decision-making technique (combination of Entropy Shannon and Vicor method) and network analysis in GIS environment. First, through GIS software, potential areas were identified for creating a continuous greenway network. Then, by using the network analysis method, the possibility of connecting the identified points in the form of a corridor was explained. In the following, the available options were scored by measuring the criteria affecting the creation of a continuous greenway network. Finally, through the method of multi-criteria analysis, the options were ranked and alternative #2 was proposed as the most likely path. The findings of this research, while stating that the field of greenways and sidewalks are aligned, showed that this area has provided spaces in the form of places with the ability to walk, which have been welcomed by users due to the existing infrastructure and facilities. In general, it is concluded that the connection of recreational and green attractions in the form of recreational green corridors, while connecting the attractions, provides an opportunity to know the neglected natural elements.